2005
DOI: 10.1074/jbc.m501473200
|View full text |Cite
|
Sign up to set email alerts
|

The Platelet-derived Growth Factor Receptor-β Phosphorylates and Activates G Protein-coupled Receptor Kinase-2

Abstract: G protein-coupled receptor kinase-2 (GRK2) serinephosphorylates the platelet-derived growth factor receptor-␤ (PDGFR␤), and thereby diminishes signaling by the receptor. Because activation of GRK2 may involve phosphorylation of its N-terminal tyrosines by cSrc, we tested whether the PDGFR␤ itself could tyrosine-phosphorylate and activate GRK2. To do so, we used wild type (WT) and Y857F mutant PDGFR␤s in HEK cells, which lack endogenous PDGFRs. The Y857F PDGFR␤ autophosphorylates normally but does not phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Our in vitro pulldown and kinase assays further confirm that GRK2 is a direct binding partner and substrate of EGFR (Figure 7). These results are in consistent with those of Wu et al (2005), who reported recently that PDGFR␤ can tyrosyl phosphorylate GRK2 directly. However, EGFR and PDGFR may employ distinct mechanisms to phosphorylate GRK2.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our in vitro pulldown and kinase assays further confirm that GRK2 is a direct binding partner and substrate of EGFR (Figure 7). These results are in consistent with those of Wu et al (2005), who reported recently that PDGFR␤ can tyrosyl phosphorylate GRK2 directly. However, EGFR and PDGFR may employ distinct mechanisms to phosphorylate GRK2.…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, Src phosphorylates and activates GRK2 (Fan et al, 2001). PDGFR-mediated GRK2 tyrosyl phosphorylation activates GRK2 and enhances GRK2-mediated seryl phosphorylation of the PDGFR, an event that reduces PDGFR signaling (Wu et al, 2005). In this study, we showed that EGF treatment regulated internalization of both ␦-and -opioid receptors through EGFR-mediated GRK2 phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 54%
“…We found that SDF-1α and ITAC resulted in significant rVSMC migration across a range of concentrations tested (Fig. 4A), with a response similar to that of other ligands known to induce rVSMC chemotaxis, such as PDGF (28).…”
Section: Cxcr7 Recruitment Of β-Arrestin Is Associated With Phosphoerkmentioning
confidence: 59%
“…In cell systems in which GRK2 mediates most of the PDGFinduced seryl phosphorylation of the PDGFR␤, persistent PDGFR␤ signaling results in down-regulation of both GRK2 (27) and the PDGFR␤ (7). To determine which widely expressed GRK (GRK2 or GRK5) mediates most of the PDGFR␤ regulation in SMCs, we first tested whether the expression level of either of these GRKs was regulated coordinately with the PDGFR␤.…”
Section: Resultsmentioning
confidence: 99%
“…To compare these PDGFR␤s under conditions of comparable GRK5 levels (Fig. 11D), we used HEK cells (which lack endogenous PDGFR␤s) (27). We used phosphorylation of PDGFR␤ Tyr 1021 and Tyr 740 as read-outs for PDGFR␤ activation.…”
Section: Pdgf-promoted Smc Migration and Proliferation Arementioning
confidence: 99%